STUDI POTENSI EUTROFIKASI DI PESISIR LOSARI MAKASSAR - Muh. Sri Yusal (JURNAL ENGGANO, 2021)
The Losari Coast zone an area located Makassar City has experienced a increase in infrastructure development to support the Makassar City Budget, Revenue and Expenditure (APBD), but density of human activities and the surrounding development has triggered a decline in water quality which is indicated by the entry of organic and inorganic wastes into the water. This study aims to assess the eutrophication potential of the Losari coast, Makassar based on the physical-chemical parameters measurement of aquatic environment. This research is quantitative descriptive with purposive sampling method. In situ and ex situ physical-chemical parameters measurement of the aquatic environment. Phosphate and Nitrate were analyzed ex situ in the laboratory using the Greenan and Olsen method which were then integrated into Indonesian Government regulations through the Ministry of Environment No. 51 of 2004. The Losari Coast zone, Makassar is an area has potential to water eutrophication which is a major threat to the life of biota and the environment around it. This is based on some physical-chemical parameters content in several Losari coastal areas have exceeded the quality standard threshold set by the Republic Indonesia Government.Keywords: Eutrophication, Water Quality, Physical-Chemical Parameters, Losari Coast. Makassar